2021
DOI: 10.1111/apt.16372
|View full text |Cite
|
Sign up to set email alerts
|

Role of smoking in functional dyspepsia and irritable bowel syndrome: three random population‐based studies

Abstract: Background: It is uncertain if functional dyspepsia (FD) or irritable bowel syndrome (IBS) are linked to smoking, and smoking cessation is not part of the routine advice provided to these patients. Aim:To assess if smoking is an independent risk factor for FD and IBS.Methods: Three population-based endoscopy studies in Sweden with 2560 community individuals in total (mean age 51.5 years, 46% male). IBS (14.9%), FD (33.5%), and associated symptoms were assessed using the validated abdominal symptom questionnair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 40 publications
1
19
0
1
Order By: Relevance
“…Psychological factors, in particular anxiety, have been reported to be associated with future development of FD in several longitudinal follow-up studies. 34 35 121 A pooled analysis of three population-based studies also identified smoking as a risk factor for PDS, 122 but not EPS. Evidence for any contribution of other lifestyle factors is conflicting.…”
Section: Presentation Of Fd Diagnosis and Management In Primary Carementioning
confidence: 99%
“…Psychological factors, in particular anxiety, have been reported to be associated with future development of FD in several longitudinal follow-up studies. 34 35 121 A pooled analysis of three population-based studies also identified smoking as a risk factor for PDS, 122 but not EPS. Evidence for any contribution of other lifestyle factors is conflicting.…”
Section: Presentation Of Fd Diagnosis and Management In Primary Carementioning
confidence: 99%
“…Additionally, smoking was associated with a significantly increased risk of IBS-diarrhea, while this only applied to the highest exposure category (20 or more cigarettes per day), there was a trend for a dose-response relationship. On the other hand, there was no relationship between IBS-C and IBS-M 20 . A systematic review found that the reported prevalence of constipation was 2.6-26.9% 21 .…”
Section: Discussionmentioning
confidence: 73%
“…Hence, the high prevalence of constipation and IBS-C (52.2%) was unexpected, suggesting that symptoms of constipation may be more common in current smokers than in the general population. Still, Talley et al 20 found that heavy smokers had significantly higher odds of diarrhea, flatus, urgency than nonsmokers. Additionally, smoking was associated with a significantly increased risk of IBS-diarrhea, while this only applied to the highest exposure category (20 or more cigarettes per day), there was a trend for a dose-response relationship.…”
Section: Discussionmentioning
confidence: 99%
“…Thirdly, we harmonized the respective exposure and outcome datasets using effect allele frequencies, while removing palindromic SNPs with intermediate allele frequencies. Lastly, according to the third assumption of MR that genetic variation cannot be associated with any possible confounding factor, we used PhenoScanner V2 [ 21 ] (a database of human genotype–phenotype associations) to search the SNPs and exclude those associated ( p < 1 × 10 −5 ) with confounding factors such as drinking [ 22 ], smoking [ 23 ], depression, and anxiety [ 24 ].…”
Section: Methodsmentioning
confidence: 99%